2013
DOI: 10.1353/csd.2013.0066
|View full text |Cite
|
Sign up to set email alerts
|

Understanding International Graduate Students’ Acculturation Using Q Methodology

Abstract: When students from other countries come to the United States to study, social, cultural, and often academic adjustments are necessary to foster their successful integration into college and university life. Using multiple theories of personal adaptability (social, emotional, cultural, communication), a Q sort of 47 statements was sorted by 21 international students studying at a Midwestern land-grant university. The procedures of Q method were followed to yield 3 resultant factors, which were interpreted as Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 31 publications
1
24
0
Order By: Relevance
“…In education, Q has been used to examine topics such as student perceptions of blended e-Education (Kim, 2012), women's attitudes toward mathematics, science, and computer science subjects (Author, 2013), undergraduate student personal epistemology toward physics (Ramlo, 2008), international students' acculturation process (Bang & Montgomery, 2013), and undergraduate student learning behavioral patterns (Author, 2014).…”
Section: Q's Position In Research Methodologymentioning
confidence: 99%
“…In education, Q has been used to examine topics such as student perceptions of blended e-Education (Kim, 2012), women's attitudes toward mathematics, science, and computer science subjects (Author, 2013), undergraduate student personal epistemology toward physics (Ramlo, 2008), international students' acculturation process (Bang & Montgomery, 2013), and undergraduate student learning behavioral patterns (Author, 2014).…”
Section: Q's Position In Research Methodologymentioning
confidence: 99%
“…Several authors (e.g., Bang & Montgomery, 2013;Cheng & Erben, 2011;Lam, 1994) borrowed the definition of acculturation from the established model, such as Schumann's acculturation model. Schumann (1986) connected acculturation to second language acquisition with its definition: "the social and psychological integration of the learner with the target language (TL) group" (p. 379).…”
Section: What Are Acculturation Adaptation and Adjustment?mentioning
confidence: 99%
“…Cheng and Erben (2011) also stated that "acculturation is an individual's process of adaptation and socialization, in which members of one cultural group accept the beliefs and manners of the host culture" (p. 479). In the same vein, Bang and Montgomery (2013) referred to acculturation as an individual's adjustment process of the interactional dynamics between two or more cultural systems.…”
Section: What Are Acculturation Adaptation and Adjustment?mentioning
confidence: 99%
“…In particular, compared with other clusters, optimists' attitude capability was right polarised, which is valued the most in their set of cross-cultural capability. People who tend to be open-minded, with a more positive attitude, may have a higher possibility of achieving emotional well-being (Bang & Montgomery, 2013). This may not explain optimists' attitude capability, as attitude capability did not seem to affect their emotion capability.…”
Section: Discussion and Analysis Of The Five Clustersmentioning
confidence: 99%
“…Lastly, cross-cultural research has identified that individuals have different profiles that display how well they adapt to the host country, such as immigrants' different cultural identities and different strategies of international students (Bang & Montgomery, 2013). A key issue is whether findings from research with immigrants can apply to immigrant entrepreneurs, as the profiles of immigrant entrepreneurs, specifically in relation to their cross-cultural capabilities, have been largely unexamined.…”
Section: Rq3 What Are the Differences Between Individuals And Generamentioning
confidence: 99%